Nuclear Resonance Vibrational Spectroscopic Definition of the Facial Triad FeIV═O Intermediate in Taurine Dioxygenase: Evaluation of Structural Contributions to Hydrogen Atom Abstraction - Srnec, Martin; Iyer, Shyam R; Dassama, Laura M K; Park, Kiyoung; Wong, Shaun D; Sutherlin, Kyle D; Yoda, Yoshitaka; Kobayashi, Yasuhiro; Kurokuzu, Masayuki; Saito, Makina; Seto, Makoto; Krebs, Carsten; et al. (Journal of the American Chemical Society, 2020)
The α-ketoglutarate (αKG)-dependent oxygenases catalyze a diverse range of chemical reactions using a common high-spin FeIV═O intermediate that, in most reactions, abstract a hydrogen atom from the substrate. Previously, the FeIV═O intermediate in the αKG-dependent halogenase SyrB2 was characterized by nuclear resonance vibrational spectroscopy (NRVS) and density functional theory (DFT) calculations, which demonstrated that it has a trigonal-pyramidal geometry with the scissile C-H bond of the substrate calculated to be perpendicular to the Fe-O bond. Here, we have used NRVS and DFT calculations to show that the FeIV═O complex in taurine dioxygenase (TauD), the αKG-dependent hydroxylase in which this intermediate was first characterized, also has a trigonal bipyramidal geometry but with an aspartate residue replacing the equatorial halide of the SyrB2 intermediate. Computational analysis of hydrogen atom abstraction by square pyramidal, trigonal bipyramidal, and six-coordinate FeIV═O complexes in two different substrate orientations (one more along [σ channel] and another more perpendicular [π channel] to the Fe-O bond) reveals similar activation barriers. Thus, both substrate approaches to all three geometries are competent in hydrogen atom abstraction. The equivalence in reactivity between the two substrate orientations arises from compensation of the promotion energy (electronic excitation within the d manifold) required to access the π channel by the significantly larger oxyl character present in the pπ orbital oriented toward the substrate, which leads to an earlier transition state along the C-H coordinate.
Keywords: železo; Dioxygenases; kyseliny ketoglutarové; Ketoglutaric Acids; Oxygen; kyslík; teorie funkcionálu hustoty; Magnetic Resonance Spectroscopy; Catalysis; Iron; Density Functional Theory; dioxygenasy; magnetická rezonanční spektroskopie; katalýza; Hydrogen; vodík